The Effect of Laser And Thermal Treatment on the Hardness and Adhesion Force on the Cermet Coating By Thermal Spray Technique - Razzaq, Ahmed Abd (Iraqi Journal of Physics, 2019)
Ceramic coating compose from a ceramic mixture (MgO, Al2O3) and metall (Al-Ni) were produced by Thermal Spray Technique. The mixed ratio of used materials Al:Ni (50%) and 40% of Al2O3 and 10% MgO. This mixture was spray on a stainless steel substrate of type (316 L) by using thermal spray with flame method and at spraying distances (8, 12, 16 and 20) cm, then the prepared films were treated by laser and thermal treatment. After that performing a hardness and adhesion tests were eximined. The present study shows that the best value of the thermal treatment is 1000 ℃ for 30 mint; the optimum spray distance is 12 cm and most suitable laser is 500 mJ where the microscopic and mechanical characterstic of coating layer get well.